Experienced, trauma-informed teachers working in remote Australia: What is required for their work to be effective? - Brown, Meegan; L’Estrange, Lyra (Frontiers in Education, 2023)
Introduction In remote education settings in Australia, experienced teachers who can effectively support students impacted by trauma are essential. Remote communities are unique yet are in many ways vulnerable to trauma as they face higher rates of disadvantage and exposure to traumatic events, including natural disasters and domestic and family violence. This is compounded by a lack of access to effective supports due to the tyranny of distance. Also, First Nations peoples living in remote areas continue to endure the ongoing and traumatic impacts of a violent and disruptive colonization. Methods The qualitative research study detailed in this article explored the requirements for the work of experienced, trauma-informed teachers in remote Australia to be effective, adding an important and unique perspective to the research evidence that is not often considered. Seven teachers from remote Australia completed a short, online questionnaire and participated in a focus group interview which was analyzed thematically. Results Themes emerging from the focus group data indicated that specific and contextualized preparation and support for teachers is required for them to do their work effectively. For remote Australian settings this means preparing teachers with cultural awareness and relevant trauma-informed training. Further, the wellbeing of these remote educators is often compromised, and addressing systemic factors such as adequate preparation of their colleagues and support to access relevant ongoing professional learning is needed. Discussion Remote teaching work in Australia is complex, and while the current study is small and exploratory in nature, the findings highlight some of the real-world impacts of these issues at a community and individual teacher level that have not been previously explored.